A new species of Caenis (Ephemeroptera: Caenidae) from Florida, USA - Pescador, Manuel L.; Richard, Barton A. (Zootaxa, 2006)
Caenis eglinensis new species is described from nymph and adults, and its relationships with other North American species of the genus are discussed.